Teaching Vocabulary through Round Robin brainstorming technique - Nurul Annisa; Andi Tenrisanna Syam; Masruddin Masruddin (Universitas Syiah Kuala, 2022)
The researcher focused on improving vocabulary achievement through the Round Robin Brainstorming technique at the seventh-grade students of SMA Negeri 5 Luwu Utara. The aim of the research was to find out whether or not the use of the Round Robin Brainstorming technique improves the vocabulary achievement of the students effectively. Pre-experimental research was used by the researcher. The population was the tenth-graders of SMA Negeri 5 Luwu Utara. The population amounted to 132 students. The Class X Ipa 1 sample consisted of 21 students. A vocabulary test was the resource of the research. The researcher gave the students a pre-test and a post-test. The data analyzed by using SPSS 22. The finding of this research shows that the use of the round-robin brainstorming technique effectively improves the students' vocabulary achievement. The students' result means score in the pre-test was lower than the mean score in the post-test (52.86 60.24). The researcher found that p-value (0.02) was lower than the alpha (0.05). The researcher concludes that using the Round Robin Brainstorming technique is effective to improve students' vocabularyThe researcher focused on improving vocabulary achievement through the Round Robin Brainstorming technique at the seventh-grade students of SMA Negeri 5 Luwu Utara. The aim of the research was to find out whether or not the use of the Round Robin Brainstorming technique improves the vocabulary achievement of the students effectively. Pre-experimental research was used by the researcher. The population was the tenth-graders of SMA Negeri 5 Luwu Utara. The population amounted to 132 students. The Class X Ipa 1 sample consisted of 21 students. A vocabulary test was the resource of the research. The researcher gave the students a pre-test and a post-test. The data analyzed by using SPSS 22. The finding of this research shows that the use of the round-robin brainstorming technique effectively improves the students' vocabulary achievement. The students' result means score in the pre-test was lower than the mean score in the post-test (52.86 60.24). The researcher found that p-value (0.02) was lower than the alpha (0.05). The researcher concludes that using the Round Robin Brainstorming technique is effective to improve students' vocabulary.